Sistem Monitoring dan Kontrol Penyiraman Aeroponik Tanaman Selada berbasis IoT dengan Metode Fuzzy Sugeno - Wibowo, Muhamad Arya Al Ghifari; Salamah, Irma; Aryanti, Aryanti (Universitas Hamzanwadi, 2024)
Dependence on optimal environmental conditions is a major challenge in aeroponic cultivation, as plant roots require regular watering to maintain moisture and nutrient absorption. This research aims to design an IoT-based aeroponic watering monitoring and control system using Sugeno fuzzy method, which can adaptively determine the duration of watering based on temperature, humidity, and light intensity sensors, and enable environmental monitoring via smartphone. This research is conducted using an experimental approach, implementing the Sugeno fuzzy inference method to generate a constant (linear) watering duration calculated based on a fuzzy rule base. The system development stages include hardware and software design, implementation of Sugeno fuzzy logic for the watering mechanism, integration of the device with an IoT platform, and testing the effectiveness of the system in maintaining optimal environmental parameters. The results showed that the developed monitoring and control system was able to produce watering duration output with an average difference to MATLAB simulation results of 0.048 milliseconds and an average error rate of 0.9%. The system is also effective in maintaining optimal humidity in the aeroponic environment, with an average humidity of 96.00% and an average temperature drop of 0.28°C every time the watering process takes place.